2017
DOI: 10.1016/j.jesp.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

From impure to harmful: Asymmetric expectations about immoral agents

Abstract: How does information about agents' past violations influence people's expectations about their future actions? We examined this question, with a focus on the contrast between past harmful and past impure actions. Participants' judgments reflected two independent influences: action consistency and expectation asymmetry. An expectation asymmetry was observed across seven studies, including two pilot studies and two supplemental studies: impure agents were judged as more likely to be harmful than harmful agents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…The present findings strengthen these associations from a different angle, showing that not only do these regions, PC and LIFG, show increased activation for harm and purity respectively, but also they represent information about the categories themselves, in the form of convergent neural representations across items within each domain. Across domains, our results further bolster a harm-purity dissociation observed previously in behavioral (Dungan and Young, 2012; Chakroff et al, 2013, 2016b; Chakroff and Young, 2015; Graham et al, 2011) and neural work (Chakroff et al, 2016a; Parkinson et al, 2011; Borg et al, 2008). Crucially, each domain was primarily encoded within at least one distinct region, suggesting that specific functional regions may handle representation of moral violation categories.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present findings strengthen these associations from a different angle, showing that not only do these regions, PC and LIFG, show increased activation for harm and purity respectively, but also they represent information about the categories themselves, in the form of convergent neural representations across items within each domain. Across domains, our results further bolster a harm-purity dissociation observed previously in behavioral (Dungan and Young, 2012; Chakroff et al, 2013, 2016b; Chakroff and Young, 2015; Graham et al, 2011) and neural work (Chakroff et al, 2016a; Parkinson et al, 2011; Borg et al, 2008). Crucially, each domain was primarily encoded within at least one distinct region, suggesting that specific functional regions may handle representation of moral violation categories.…”
Section: Discussionsupporting
confidence: 87%
“…Did she do it on purpose (Young et al, 2007)? At a higher level, the act may be represented as an instance of a more abstract conceptual category, such as ‘harm-based’ or ‘purity-based’ violations, and judged accordingly (Graham et al, 2012; Dungan and Young, 2012; Chakroff et al, 2016b). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially important to consider given that recent research has revealed that people may view someone who commits a harmless yet impure action as having greater potential for future harm. That is, impure actions may cause people to judge the person as generally harmful (see Chakroff, Russell, Piazza, & Young, ; Pizarro & Tannenbaum, ; Pizarro, Tannenbaum, & Uhlmann, ). We also sought to account for the various manifestations of harm/care.…”
Section: Purity and Loyalty In Sexual And Relational Contextsmentioning
confidence: 99%
“…This is especially important to consider given that recent research has revealed that people may view someone who commits a harmless yet impure action to have greater potential for future harm. That is, impure actions may cause people to judge the person as generally harmful (see Chakroff, Russell, Piazza, & Young, 2017;Pizarro, Tannenbaum, & Uhlmann, 2012). We also sought to account for the various manifestations of harm/care.…”
Section: The Present Studiesmentioning
confidence: 99%